2016
DOI: 10.1016/j.juro.2016.04.114
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Sparing, Robot-Assisted Radical Cystectomy with Intracorporeal Bladder Substitution in the Male

Abstract: In the hands of an experienced surgeon nerve and seminal vesicle sparing robot-assisted radical cystectomy with intracorporeal reconstruction of the neobladder seems feasible and safe. It provides short-term oncologic efficacy and promising functional outcomes. Yet comparative, long-term followup studies with standard open cystectomy are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 28 publications
3
46
1
1
Order By: Relevance
“…showed that 74% and 88% of patients achieved daytime continence (1 pad per day) for 6 and 12 months, respectively, whereas Asimakopoulos et al . showed that 75% and 100% of patients experienced daytime continence (0 pad per day) for 1 and 12 months, respectively . Recently, Kouk et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that 74% and 88% of patients achieved daytime continence (1 pad per day) for 6 and 12 months, respectively, whereas Asimakopoulos et al . showed that 75% and 100% of patients experienced daytime continence (0 pad per day) for 1 and 12 months, respectively . Recently, Kouk et al .…”
Section: Introductionmentioning
confidence: 99%
“…and Asimakopoulos et al . reported that 45% and 77.5% of patients, respectively, who received nerve‐sparing RARC achieved potency . Tyritzis et al .…”
Section: Introductionmentioning
confidence: 99%
“…The pelvic autonomic nerves, specifically the sympathetic fibres, are known to control urethral tonus at rest and assure urinary continence . A beneficial impact of nerve sparing (NS) on urinary continence after urinary diversion with an OBS has been reported in a few open and robot‐assisted RC series with short to mid‐term follow‐up . However, the debate is ongoing as to whether NS affects long‐term outcomes because it is unknown whether the positive impact of NS persists over time.…”
Section: Introductionmentioning
confidence: 99%
“…RCTs with sufficient power are awaited. Table shows the available RARC studies of neobladders with published functional outcomes …”
Section: Functional Outcomesmentioning
confidence: 99%